Biopsychosocial determinant of quality of life of older adults in Pakistan and Canada - Batool, Syeda Shahida; Tanveer, Samra; Chatrath, Sarvjeet Kaur; Batool, Syeda Azra (Frontiers in Psychiatry, 2024)
Background: Rapidly rising average age of the older adults has brought various global healthcare challenges. A core challenge is how to enhance their quality of life (QoL). Objective: the objective of the current study was to test the significance of biopsychosocial determinants of quality of life of older adults in Pakistan and Canada. Methodology: A cross sectional survey was carried out on a conveniently approached purposive sample of 1005 older adults (Pakistani = 557 and Canadian = 448) of age ranged between 60 and 80 years. The data were via demographic datasheet, World Health Organization Quality of Life Brief Scale, Health and Lifestyle Questionnaire, General Self-Efficacy Scale, Rosenberg Self-Esteem Scale and Berlin Social Support Scale. Results: The results of hierarchical regression analysis showed that biopsychosocial factors (viz., health and life style, chronic illness, self-efficacy, self-esteem, and social support) significantly predicted (R2 = .27, and .68) quality of life of older adults in Pakistan and Canada respectively, after controlling the demographic variables. Significant differences were found between Pakistani and Canadian older adults on biopsychosocial factors: Canadian older adults scored significantly higher on health and lifestyle, self-efficacy, and quality of life, and older adults in Pakistan scored significantly higher on self-esteem and social support. Conclusion: A significant amount of better QoL of older adults can be achieved through enhancing the biopsychosocial correlates of their QoL, both in Pakistan and Canada.